- Z = f(A,B,C) = + B + AB + AC
- = (B + ) + A(C + B)
- = (B + ) + A(C + B) from T10b
- = B + + AC + AB
- = B( + A) + + AC from T9a and T8b
- = B + + AC
Z = f(A,B,C,D) = B + B + BC + A

- = B + B(C + ) + (B + A) using B (twice) T4a
- = B + B + (B + A) from T9a, T8b and T10b
- = B(1 + ) + B + A from T8a
- = B + B + A from T8a
- = B(1 + + A
- = B + A from T8a
- Z = f(A,B,C,D) = AB + ABD + AD + ABCD + ACD + ABC + AC
- = AB + ABC + AC + AD from T9a and T8b
- = AB + AC + AD from T9a and T8b
- = A(B + D) + AC
- = A(B + D) + AC from T10a
- = AB + AD + AC

Return

To submit your questions and queries please click here: